Dynamic single-site polysulfide immobilization in long-range disorder Cu-MOFs. Issue 69 (31st July 2020) - Sun, Ju; Lu, Xinxin; Wu, Kuang-Hsu; Hou, Jingwei; Fang, Ruopian; Hart, Judy N.; Zhu, Shenmin; Chen, Vicki; Amal, Rose; Wang, Da-Wei
Abstract : The dynamic structural transformation of Cu-MOFs during cell discharge and recharge involves irreversible frame-work amorphization and interconvertible single copper cations. Abstract : The structural transformation of MOFs in a polysulfide electrode process is poorly understood. We report the electrochemical amorphization of Cu3 (BTC)2 MOFs in polysulfide electrolyte. We unveil the dynamic single-site polysulfide immobilization at the interconvertible Cu 2+ /Cu + cation centres upon polysulfide adsorption and desorption, along with the reversible distortion of the Cu–O square planar unit.